PEMBIASAN ANTARA ACT OF STATE DOCTRINE DAN KEKEBALAN JURISDIKSI - BAMBANG PURWANTO (Universitas Mahasaraswati K. Mataram, 2023)
In international law, the principle of state jurisdiction is recognized, wherein a state has the right to apply its laws within its territory to individuals, objects, and events. In practice, this principle can affect the implementation of state sovereignty. The once absolute sovereignty of a state becomes limited by the presence of other states, thus weakening the theory of absolute immunity. The weakening of the theory of absolute immunity also automatically impacts sovereign immunity, presenting challenges for a state in exercising its jurisdiction, especially in adjudicating cases involving actions in other countries. In an effort to balance the impact of weakened sovereign immunity in international law, a theory introduced by the United States emerged, known as the Act of State Doctrine. This theory seemingly provides a secondary protection for states in enforcing their laws. However, there is a resemblance between the theory of sovereign immunity and the Act of State Doctrine in scope and limitations, leading to confusion in interpretation. Therefore, clear discussions are necessary to provide a sharper understanding of both theories.